Tafsir Bil Matsur: Study of the Literature of Social Validity: Tafsir Bil Matsur: Studi tentang Sastra Validitas Sosial - Muhamad Aidul Mubarok; Pendi Nurul Azmi (Senarai: Journal of Islamic Heritage and Civilization, 2025)
Tafsir bil Ma'tsur is a method of interpreting the Qur'an that relies on authoritative sources such as the interpretations of Prophet Muhammad (PBUH), his companions, and the tabi'in (the generation following the companions). This type of exegesis developed during the time of the Prophet and continued to be used by subsequent generations, with interpretations derived directly from the Prophet’s explanations or through the companions' narrations. Initially, this interpretation was transmitted orally before being codified into a distinct discipline. Throughout its history, Tafsir bil Ma'tsur underwent two phases: oral transmission and written codification, which expanded its scope. This method of interpretation is highly regarded for utilizing primary, reliable sources, though it has sparked debate among scholars regarding the status of the tabi'in’s statements in exegesis. Some scholars argue that the statements of the tabi'in fall under Tafsir bil Ma'tsur, while others classify them as Tafsir bil Ra'yi (interpretation based on reasoning). Nevertheless, Tafsir bil Ma'tsur is considered obligatory to follow as long as its transmission is free from errors and it is widely accepted by scholars